![](https://rs.olm.vn/images/avt/0.png?1311)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
a) x + 1/15 = 1/3 - 1/4 = 4/12 - 3/12 = 1/12.
=> x = 1/12 - 1/15 = 5/60 - 4/60 = 1/60.
b) x - 5/12 = 1/3 + 1/4 = 4/12 + 3/12 = 7/12.
=> x = 7/12 + 5/12 = 1
c) x x 2/7 = 3/4 x 4/15 = 1/5
=> x = 1/5 : 2/7 = 1/5 x 7/2 = 7/10
d) x : 3/8 = 4/3 : 3/6 = 4/3 x 2 = 8/3
=> x = 8/3 x 3/8 = 1
![](https://rs.olm.vn/images/avt/0.png?1311)
4/7 + x = 2
x = 2 - 4/7
x =10/7
1 3/4 - x = 3/4
x =1 3/4 - 3/4
x = 1
2/3 . (x-1/3)=4/5
x - 1/3 = 4/5 : 2/3
x - 1/3 = 6/5
x = 6/5 + 1/3
x = 23/15
![](https://rs.olm.vn/images/avt/0.png?1311)
1, 54 : x - 1 = 5
54 : x = 5+1 = 6
x = 54 : 6 = 9
2, 42 : x + 0 = 8
x = 42 : 8 = 21/4
3, 24 : x - 8 = 0
24 : x = 0 + 8 = 8
x = 24 : 8 = 3
Tk mk nha
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
a)1/3+1/4+2/3+3/4
=(1/3+2/3)+(1/4+3/4)
=1+1
=2.
b)1/2+1/3-1/5+1/6
=(1/2+1/3+1/6)-1/5
=1-1/5
=4/5
c)2/3x4/5+1/3x4/5
=4/5x(2/3+1/3)
=4/5x1
=4/5
d)2/3x4/5-1/3x4/5
=4/5x(2/3-1/3)
=4/5x1/3
=4/15
![](https://rs.olm.vn/images/avt/0.png?1311)
1. 41/7 - x = 25/9
=> x = 41/7 - 25/9
=> x = 194/63
2. 3x = 12,8
=> x = 12,8 : 3
=> x = 64/15
3. 41/2 x = 5
=> x = 5: 41/2
=> x = 10/41
4. 3/4 x = 1
=> x = 1: 3/4
=> x = 3/4
5. 4/5 : x = 3
=> x = 4/5 : 3
=> x = 4/15
6. 12/x = 4
=> x = 12/4
=> x = 3
7. 4/7 : x = 4/7
=> x = 4/7 : 4/7
=> x = 1
8. 2x - 3/4 = 7/8
=> 2x = 7/8 + 3/4
=> 2x = 13/8
=> x = 13/8 : 2
=> x =13/16
Ruby Chan :))
1, \(4\frac{1}{7}-x=2\frac{5}{9}\)
\(\frac{4\times7+1}{7}-x=\frac{2\times9+5}{9}\)
\(\frac{29}{7}-x=\frac{23}{9}\)
\(x=\frac{29}{7}-\frac{23}{9}\)
\(x=\frac{261}{63}-\frac{161}{63}\)
\(x=\frac{100}{63}\)
2, \(3\times x=12,18\)
\(x=12,18\div3\)
\(x=4,06\)
3, \(4\frac{1}{2}\times x=5\)
\(\frac{4\times2+1}{2}\times x=5\)
\(\frac{9}{2}\times x=5\)
\(x=5\div\frac{9}{2}\)
\(x=\frac{5\times2}{9}=\frac{10}{9}\)
4, \(\frac{3}{4}\times x=1\)
\(x=1\div\frac{3}{4}\)
\(x=\frac{1\times4}{3}=\frac{4}{3}\)
5, \(\frac{4}{5}\div x=3\)
\(x=\frac{4}{5}\div3\)
\(x=\frac{4}{5\times3}=\frac{4}{15}\)
6,\(\frac{12}{x}=4\)
\(x=12\div4\)
\(x=3\)
7, \(\frac{4}{7}\div x=\frac{4}{7}\)
\(x=\frac{4}{7}\div\frac{4}{7}\)
\(x=1\)
8, \(2x-\frac{3}{4}=\frac{7}{8}\)
\(2x=\frac{7}{8}+\frac{3}{4}\)
\(2x=\frac{7}{8}+\frac{6}{8}\)
\(2x=\frac{13}{8}\)
\(x=\frac{13}{8}\div2\)
\(x=\frac{13}{8\times2}=\frac{13}{16}\)
- \(\dfrac{3}{4}\)\(x\) - 3 = \(\dfrac{1}{4}\)\(x\)
\(\dfrac{1}{4}\)\(x\) + \(\dfrac{3}{4}\)\(x\) = - 3
\(x\) = - 3